DELTAMETRINA E FENTION EM ENSAIO CONTRA O CUPIM DE MONTE (Cornitermes cumulans (KOLLAR, 1832) (ISOPTERA: TERMITIDAE) - Mariconi, F. A. M.; Hamamura, R.; Rangel, R. C.; Regitano, E. B.; Clari, A. I.; Rangel, M. C. (REVISTA DE AGRICULTURA, 2015)
DELTAMETRINA E FENTION EM ENSAIO CONTRA O CUPIM DE MONTE (Cornitermes cumulans (KOLLAR, 1832) (ISOPTERA: TERMITIDAE)